Finite Element Analysis of Ramshorn Hook Using CAE Tools - Bhagel Singh, Prabhat Singh (International Journal of Advanced Science and Technology, 2020)
Ramshorn hook is a category of crane hook with double slings are mounted one shank. Ramshorn hooks are basically used to lift the heavy loads in various industries for heavy duties. Ramshorn hook are designed with smaller saddles than the single hook for same lifting capacity. These are suitable for heavy lifting applications. The present work has been carried out on a forged Ramshorn hook. An effort has been made to analyses the Ramshorn hook of 40 tone capacity. The CAD model of Ramshorn hook is initially prepared using SolidWorks according to IS codes. The finite element analysis of this CAD model has been carried out using ANSYS in order to investigate maximum stresses. Discrete stresses have been determined by applying WinklerBach equation. Good correlations have been found between analytical and CAE results obtained, validating the model.